Neuroprotective effects of curcumin-loaded nanophytosome on ketamine-induced schizophrenia-like behaviors and oxidative damage in male mice. (20th November 2021) - Moghaddam, Akbar Hajizadeh; Maboudi, Khadijeh; Bavaghar, Bita; Sangdehi, Seyed Reza Mokhtari; Zare, Mahboobeh
Highlights: CNP prevented ketamine-induced schizophrenia-like behaviors. CNP shows higher efficacy over free curcumin to improve ketamine-induced oxidative stress. CNP ensures a targeted delivery with enhanced bioavailability. Abstract: Curcumin as an antioxidant natural herb has shown numerous pharmacological effects. However, the poor bioavailability of curcumin is a significant pharmacological barrier for its antioxidant activities. The present study was conducted to develop curcumin-loaded nanophytosome (CNP) and explore their therapeutic potential in a ketamine (KET)-induced schizophrenia (SCZ) model. The mice in our experiment were treated orally with curcumin and CNP (20 mg/kg) for 30 consecutive days. In addition, the animals received intraperitoneal injection of KET (30 mg/kg/day) from the 16th to the 30th day. SCZ-like behaviors were evaluated employing forced swimming test (FST), open field test (OFT), and novel object recognition test (NORT), and oxidative stress markers in the brain were estimated. Our results revealed that CNP has a greater neuroprotective effect compared to free curcumin. CNP pretreatment significantly ameliorated KET-induced brain injury evidenced by a marked reduction in the depressive and anxiety-like behaviors, memory deficits, and oxidative stress markers in cortical and subcortical tissues. Therefore, CNP, as a suitable drug delivery system, may improve curcumin bioavailability and confer stronger neuroprotective effects against KET-induced behavioral deficits and oxidative damages.